2015
DOI: 10.1530/eje-14-0911
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance in patients with type 1 diabetes assessed by glucose clamp studies: systematic review and meta-analysis

Abstract: Objective: The aim of this study was to perform a systematic review and meta-analysis on insulin resistance in adult patients with type 1 diabetes mellitus compared to healthy controls, assessed by hyperinsulinemic euglycemic clamp studies. Design and methods: We conducted a systematic search of publications using PubMed, EMBASE, Web of Science and COCHRANE Library. Hyperinsulinemic euglycemic clamp studies comparing adult patients with type 1 diabetes mellitus to healthy controls were eligible. Primary outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(63 citation statements)
references
References 52 publications
2
59
0
2
Order By: Relevance
“…A meta‐analysis of 65 studies, which included 516 325 adults without diabetes, has shown that insulin resistance, measured by homeostatic model assessment, is a good predictor of cardiovascular disease . In line with these findings, insulin resistance in T1D has been associated with increased risk of cardiovascular disease . Furthermore, the CACTI study demonstrated that insulin resistance, measured by clamp techniques, predicted the presence of coronary artery calcification in people with T1D …”
Section: Definition Of Ddmentioning
confidence: 81%
See 2 more Smart Citations
“…A meta‐analysis of 65 studies, which included 516 325 adults without diabetes, has shown that insulin resistance, measured by homeostatic model assessment, is a good predictor of cardiovascular disease . In line with these findings, insulin resistance in T1D has been associated with increased risk of cardiovascular disease . Furthermore, the CACTI study demonstrated that insulin resistance, measured by clamp techniques, predicted the presence of coronary artery calcification in people with T1D …”
Section: Definition Of Ddmentioning
confidence: 81%
“…For example, repeated hypoglycaemia or even the fear of hypoglycaemia results in maladaptive eating habits that favour the development of obesity . Peripheral insulin resistance precipitated by subcutaneous insulin administration rather than the physiological portal vein delivery, is another additional factor in the development of DD . DD in people with T1D, therefore, develops secondary to a combination of lifestyle behaviour akin to individuals without diabetes, and diabetes‐specific mechanisms related to hypoglycaemia, and the non‐physiological administration of insulin subcutaneously.…”
Section: Pathogenesis Of Ddmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are a number of commonalities between T1D and T2D that are worth considering. First, insulin resistance is a risk factor for both T1D (Donga, et al 2015; Fourlanos, et al 2004) and T2D (Kahn 1998; Samuel and Shulman 2016). Second, pro-inflammatory cytokines (e.g., IL-1β, IFN-γ, TNF-α, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Although T1DM is primarily a disease of insulin deficiency, T1DM patients are insulin-resistant compared with non-diabetic subjects; with insulin resistance observed both during puberty and in those with long-standing T1DM345678. While insulin resistance in T1DM was previously thought to be directly related to adiposity and elevated HbA1c389, recent evidence has demonstrated insulin resistance in multiple tissues of those with T1DM despite good glycemic control and a BMI similar to that of non-diabetics1011.…”
mentioning
confidence: 99%